GAMBARAN DUKUNGAN KELUARGA TERHADAP KEPATUHAN PASIEN GAGAL GINJAL KRONIK MENJALANI HEMODIALISIS DI RSUP HAJI ADAM MALIK MEDAN TAHUN 2021 - Rusmauli Lumban Gaol; Tekken Pebruanto Nahampun (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Chronic kidney failure is kidney damage that causes the kidneys to be unable to remove toxins and waste products from the blood, characterized by the presence of protein in the urine and a decrease in the glomerular filtration rate, lasting more than 3 months. Family support is an attitude of action and family acceptance of supportive family members who are always ready to provide help and assistance if needed, in this case the acceptance of family support will know that there are other people who pay attention, appreciate and love them. Obedience is obedience or disobedience to orders, rules and discipline. Changes in individual attitudes and behavior start from the stage of compliance, identification, then internalization. Hemodialysis is a life-saving procedure performed by nephrology nurses to patients with impaired kidney function. The purpose of the study was to determine the description of family support for patients undergoing hemodialysis at Haji Adam Malik General Hospital Medan in 2021. This study used a descriptive method. The population in this study were all patients with chronic renal failure undergoing hemodialysis. The sampling technique used was consecutive sampling as many as 74 respondents. The results of research conducted at Haji Adam Malik General Hospital Medan as follows: family support for chronic kidney failure patients undergoing hemodialysis at Haji Adam Malik General Hospital Medan are mostly good categories as many as 70 respondents (94.6%), chronic kidney failure patient compliance in undergoing hemodialysis at Haji Adam Malik General Hospital in Medan, most of the good categories were 48 respondents (48.9%). Family support for patients and patient compliance with hemodialysis are in the good category, strongly supported by education because the higher a person's education, the faster he understands about the condition of the disease he is experiencing.